Խարկովում Խորհրդային Հայաստանի լիազօր ներկայացուցիչ Յովսէփ Կարախանեանի նամակ-զեկուցագրերն Ուկրաինայի հայերի մասին (1921—1922 թթ.) - Սուքիասեան, Համօ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Оценивая важность развития дружественных отношений с Советской Украиной, весной 1921 года власти Социалистической Советской Республики Армения (ССРА) решили установить дипломатические отношения и начать взаимовыгодное сотрудничество с Украиной, сосредоточив внимание на проблемах тысяч западных армянских беженцев, нашедших там приют после геноцида. 23 мая 1921 года Совет Народных Комиссаров Советской Армении назначил Овсепа Караханяна полномочным представителем ССРА на Советской Украине. Армянское представительство располагалось в столице страны Харькове. О. Караханян периодически информировал правительство о своей деятельности. Он направил в Наркомат иностранных дел в Ереване около десятка писем, имеющих особое значение для изучения армяно-украинских отношений в 1921—1922 годах. Они до сих пор не опубликованы и хранятся в Национальном архиве Армении. В этих письмах раскрывается деятельность представительства, направленная на защиту интересов армян, проживающих на Украине. Согласно этим письмам, большую часть армянской общины Харькова составляли выходцы из Западной Армении, поэтому одним из важных вопросов, стоящих перед Караханяном, было решение проблем тысяч соотечествеников. Особенно остро стоял вопрос о гражданстве беженцев: украинские власти обсуждали его с точки зрения турецко-украинских отношений. Вышеупомянутые письма-отчеты являются надежным источником для изучения истории армян Украины. Некоторые из вопросов, обсуждаемых в письмах, актуальны и в настоящее время. Assessing the importance of developing friendly relations with Soviet Ukraine, in the spring of 1921, the authorities of the Armenian Soviet Socialist Republic (ASSR) decided to establish diplomatic relations and start mutually beneficial cooperation with Ukraine, focusing on the problems of thousands of Western Armenian refugees who had found shelter there. On May 23, 1921, the Council of People's Commissars of Soviet Armenia appointed Hovsep Karakhanyan as the plenipotentiary of the ASSR in Soviet Ukraine. The Armenian representative office was located in Kharkov, the capital of the country. H. Karakhanyan periodically informed his superiors about his activities. He sent about a dozen of letters to the People’s Commissariat of Foreign Affairs in Yerevan, which are of special importance for the study of Armenian-Ukrainian relations in 1921—1922. They have not been published so far and are kept in the National Archives of Armenia. These letters reveal the activities of the representative office aimed at protecting the interests of Armenians living in Ukraine. According to the letters, the majority of the Armenian community in Kharkov were immigrants from Western Armenia, so one of the important issues facing Karakhanyan was to solve the problems of thousands of Armenian refugees. The issue of their citizenship was particularly acute: the Ukrainian authorities discussed it from the point of view of Turkish-Ukrainian relations. The above-mentioned letter-reports are a reliable source for studying the history of the Armenians of Ukraine. Some of the issues discussed in the letters are still relevant today.
Keywords: Պատմութիւն; Սփիւռքահայութիւն